Maturation of the Acute Hepatic TLR4/NF-κB Mediated Innate Immune Response Is p65 Dependent in Mice - Zarate, Miguel A.; Nguyen, Leanna M.; De Dios, Robyn K.; Zheng, Lijun; Wright, Clyde J. (Frontiers in Immunology, 2020)
Compared to adults, neonates are at increased risk of infection. There is a growing recognition that dynamic qualitative and quantitative differences in immunity over development contribute to these observations. The liver plays a key role as an immunologic organ, but whether its contribution to the acute innate immune response changes over lifetime is unknown. We hypothesized that the liver would activate a developmentally-regulated acute innate immune response to intraperitoneal lipopolysaccharide (LPS). We first assessed the hepatic expression and activity of the NF-κB, a key regulator of the innate immune response, at different developmental ages (p0, p3, p7, p35, and adult). Ontogeny of the NF-κB subunits (p65/p50) revealed a reduction in Rela (p65) and Nfkb1 (p105, precursor to p50) gene expression (p0) and p65 subunit protein levels (p0 and p3) vs. older ages. The acute hepatic innate immune response to LPS was associated by the degradation of the NF-κB inhibitory proteins (IκBα and IκBβ), and nuclear translocation of the NF-κB subunit p50 in all ages, whereas nuclear translocation of the NF-κB subunit p65 was only observed in the p35 and adult mouse. Consistent with these findings, we detected NF-κB subunit p65 nuclear staining exclusively in the LPS-exposed adult liver compared with p7 mouse. We next interrogated the LPS-induced hepatic expression of pro-inflammatory genes (Tnf, Icam1, Ccl3, and Traf1), and observed a gradually increase in gene expression starting from p0. Confirming our results, hepatic NF-κB subunit p65 nuclear translocation was associated with up-regulation of the Icam1 gene in the adult, and was not detected in the p7 mouse. Thus, an inflammatory challenge induces an NF-κB-mediated hepatic innate immune response activation across all developmental ages, but nuclear translocation of the NF-κB subunit p65 and associated induction of pro-inflammatory genes occurred only after the first month of life. Our results demonstrate that the LPS-induced hepatic innate immune response is developmentally regulated by the NF-κB subunit p65 in the mouse.